Utilization of Alikhtibar Media for Language Learning in Mahaad Tahfidz Arabic Al Gontory Lil Banat, Malaysia - Himmah Nabilah Syifa; Romlah Hamidah; Salman Al Farizi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study aims to evaluate the effectiveness of using Alikhtibar media in language learning at Mahaad Tahfiz Arabic Al Gontory Lil Banat, Malaysia. The activities involved 75 participants in the introduction and direct trial session on March 18, 2024, as well as first and second-grade high school equivalent students who attended the training on March 19, 2024.The results of this study indicate that the use of Alikhtibar media can improve students' listening, reading, and writing skills in Arabic. The exercises included listening to audio from native speakers, reading Arabic texts, and writing words or sentences in Arabic. The evaluation methods used were multiple choice, matching empty answers, filling in blanks, and drag and drop. The recommendation from this study is the broader implementation of Alikhtibar media in the Arabic language curriculum in other educational institutions. The use of interactive media and digital technology has proven effective in enhancing language skills and students' learning motivation. This implementation is expected to significantly contribute to improving the quality of language learning in educational institutions.